The Point of View of Undergraduate Health Students on Interprofessional Collaboration: A Thematic Analysis. (April 2019) - Bianchi, Monica; Bagnasco, Annamaria; Ghirotto, Luca; Aleo, Giuseppe; Catania, Gianluca; Zanini, Milko; Carnevale, Franco; Sasso, Loredana
Interprofessional education (IPE) is essential to prepare future professionals for interprofessional collaboration (IPC). Learning together is essential for students because it is a way to understand the roles of other colleagues, improve their skills, knowledge, competencies, and attitudes to collaborate with the interprofessional teams. To explore how undergraduate students who attend IPE courses define IPC, a qualitative study using semistructured interviews followed by a thematic analysis was performed. Four main themes were identifed: IPC as a resource, requirements for IPC, emotions linked to IPC, and tutor's role to facilitate students' perception of IPC. Students considered IPE important to build IPC, where clinical placement tutors play a key role. The most important findings of the present study include the students' considerations about the importance of IPE when building their IPC definition and the key role played by the tutor during the placement in building IPC in clinical practice.